Visitors' viewpoint on sustainable ecotourism in tilagor eco park of Sylhet, Bangladesh (Journal of the Sylhet Agricultural University, 2025)
Sustainable ecotourism promotes an optimal balance between economic benefits, environmental conservation, and sociocultural preservation in developing countries. Thus, the purpose of the study is to determine the visitors’ viewpoint on sustainable ecotourism and its impacts on the local economy, environment, and society. It strengthens Bangladesh's attempts to protect its wildlife. The study was carried out in Bangladesh's Sylhet district at the Tilagor Eco Park from April 2023 to February 2024. A structured questionnaire comprising demographic variables and impacts categorized into economic, environmental, and sociocultural categories was used to interview 105 visitors. Although random, the sampling strategy was impartial. The result of the study showed that ecotourism is especially popular among young people. The main attraction of Tilagor Eco Park was the forest setting, which 93.3% of visitors agreed upon. The majority of the visitors were satisfied and faced no problems while visiting (65.7%) the park. 95.2% of visitors agreed that the community would benefit from the development of a framework for sustainable tourism, and 87% thought that increasing employment opportunities and supporting local cultural activities would benefit the local economy. Most visitors feel increasing local awareness is necessary, emphasizing the connection between ecotourism and conservation. Through infrastructure development tourism can cause soil erosion and damage vegetation. The study revealed that without compromising ecotourism's environmental and aesthetic aspects, visitors recognize the economic and sociocultural benefits it conveys.J. Sylhet Agril. Univ. 11(1): 37-46, 2024